Policy Simulation of Fuel Subsidy Reduction and Impact on Strategic Sectors (Input Output Analysis) - Gumilar Achmad Ramadhan; Wahyudi Kumorotomo; Mulyadi Sumarto; Agus Joko Pitoyo (Universitas Pancasakti Tegal, 2019)
Subsidy policies are needed to maintain people's purchasing power, but some argue that subsidies are not productive so they must be eliminated. This research tries to find a middle ground between the two opinions, namely the reduction of subsidies. Subsidy spending on the APBN 2019, including subsidies on fuel, LPG, electricity and non-energy subsidies. This study discusses the simulation of a policy to adjust fuel subsidies, which results in fuel prices, and predicts their impact on other sectors. The research method was carried out with an Input Output analysis, then in-depth interviews with related parties. This study implements sensitivity analysis with three different simulations, namely the impact of 10%, 20%, and 30% increase in fuel prices on strategic sectors, including Mining and Quarrying, Manufacturing Industry, Construction, Corporate Services and Transportation and Warehousing. The most affected sector was the Mining and Quarrying sector, while the highest affected Output was the Manufacturing Industry sector. The direct impact of the increase in fuel prices was felt on the Transportation and Warehousing sector, as one of the basic consumer goods whose prices were stabilized by the government to be affordable to the public. The increase in the price of this sector causes an increase in the prices of other sectors, for example an increase in transportation costs will encourage food increases, as a result of higher distribution costs from sellers to customers.